A position statement and recommendations for sustainable kidney care - Jihyun Yang; So Mi Kim; Eunjeong Kang; Harin Rhee; Jwa-Kyung Kim; Jung-Kook Wi; Ju-Young Moon; Yoosun Joo; Yohan Park; Young-Hwan Hwang; Kyungho Choi; Younglim Kho; et al. (Kidney Research and Clinical Practice, 2025)
The Korean Society of Nephrology has embraced the principle of "Green Nephrology" and launched campaigns addressing environmental sustainability in kidney care. These include initiatives to monitor resource usage, reduce waste generation in treatment facilities, and minimize dialysis-related environmental effects. The Society aims to raise awareness about the environmental impact of kidney disease and its treatments while emphasizing the importance of sustainable practices. Collaboration between health authorities and related academic societies is planned for the development of national strategies. The Special Committee on Sustainable Renal Treatment published the "Sustainable Kidney Care Recommendations," which provides guidelines for efficient measures to reduce the environmental footprint of dialysis. This effort aims to inspire systematic, practical, and sustainable healthcare solutions.